Serum B cell activating factor and interleukin 10 levels in common variable immunodeficiency: relationship with clinical findings - Mijanovic, Radovan; Andrejevic, Sladjana; Jurisic, Vladimir; Bonaci-Nikolic, Branka (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Common variable immunodeficiency (CVID) is an immunologically and clinically heterogeneous disorder. Disturbed cytokine production is implicated in dysfunctional immune response. The aim of this study was to investigated B-cell activating factor (BAFF) and interleukin (IL)-10 levels in CVID patients. Methods. The study included 28 CVID patients diagnosed and followed during a 20-year period (mean follow-up 14.5 years). Control groups consisted of 4 patients with X-linked agammaglobulinemia (XLA) and 21 healthy subjects. According to clinical characteristics, the CVID patients were divided into four groups which partly overlap: chronic pulmonary diseases (n = 21), splenomegaly (n = 13), autoimmune diseases (n = 9) and patients with recurrent infections despite regular intravenous immunoglobulin (IVIg) substitution (n = 4). The serum levels of BAFF and IL-10 were measured by commercial ELISA. Results. The BAFF levels were found to be higher in all CVID patients compared to the healthy controls (p
Keywords: common variable immunodeficiency; b-cell activating factor; cytokines; interleukins; lung diseases; splenomegaly; autoimmune diseases